PENGARUH MOTIVASI, KETERAMPILAN DAN PENGETAHUAN PEMASARAN TERHADAP PRODUKTIVITAS MASYARAKAT DI BANDUNG - INDONESIA - Nani Dewi Sunengsih (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2019)
Abstract. The study aims to determine the effect of motivasioanl, skill and marketing knyowledge on produktiv. The study uses a survey method with causal analysis (path analysis). The sample consisted of 100 housewives by using simple randam sampling technique. The relationship model between variables formulated in the theoretical model using Analysis of Variance (ANOVA). The results showed that variations of the productivity of the people were directly affected positively by variations of motivation, skills, and marketing knowledge. Variations of marketing knowledge are directly affected positively by variations of motivation and skills. Therefore, to increase community productivity can be done by increasing marketing knowledge, motivation, and skills. This can be done by enhancement program through community-based instructional design.